Nós, a gente e o clítico se como estratégias de indeterminação do sujeito no Português - Oliveira, Karine Rios de (2006)
In this work some strategies of subject indeterminacy were synchronically analyzed in the light of the Quantitative Sociolinguistic and the Parametric Sociolinguistic: the pronominal forms nós and a gente, and the clitic se followed by a verb in the infinitive form. The usage of such strategies is different in Brazilian Portuguese (BP) and in European Portuguese (EP) owing to the tendency of fulfilling the subject position which the former has presented. In this meaning, nós, a gente and se+infinitive were investigated so in BP, as in EP. For that, corpuses of spoken language of both varieties were used. For the composition of corpus of BP oral language, we used 45 interviews (on hour each) carried out with speakers (from both sex) from the city of Uberlândia/MG, selected according to the variacionist model conforming social class and age group. As corpus of EP spoken language, we used interviews which are available in the Instituto Camões site and in the site of the Projeto Corpus de Referência do Português Contemporâneo. The samples were codified from six linguistic factors and two social factors: variety of Portuguese, kind of sentence, presence/absence of previous indeterminate form, presence/absence of modalization, number of arguments, presence/absence of preposition, social class and age group. By means of crossing codified data in Varbrul Program, we can inquire: the usage tendency of strategy a gente in BP; and in EP, the occurrence of a gente and nós; and that se+infinitive is not the most favored indeterminate form in none of these Portuguese varieties. The study of the strategies shows that the pronoun nós is kept as an indeterminate form in EP, in which it occurs as a favored strategy beside a gente. The Portuguese varieties presented distinct frequencies concerning to the variants nós and a gente usage: the pronoun nós was more frequent in EP, and the form a gente was more frequent in BP. These results can be explained by the pronominal reorganization process that BP has gone through.